The role of innovative work behavior and organizational support for business model innovation - Marianne Hock-Doepgen; Jana Sophia Montasser; Sascha Klein; Thomas Clauss; Adnan Maalaoui (R&D Management, 2024)
While innovative work behavior sets the stage for organizational innovativeness, little is known about how innovative work behavior is related to business model innovation. This study analyzes how employees' innovative work behavior leads to business model innovation. Following the organizational support theory, we further examine that business model innovation is a function of individual innovative work behavior of the employee and the firm's ability to create an organizational environment in which these work behaviors can unfold and be translated into innovative output, such as business model innovation. Based on survey data from 154 firms, this study empirically finds that employee innovative work behavior is positively related to business model innovation. Further, we find that the effect of innovative work behavior on business model innovation is moderated through organizational support for innovation. However, the moderation reveals different results for low levels of innovative work behavior than for high values. For high values, we find that additional organizational support does not lead to more business model innovation.
Keywords: 650